Nonvitamin and Nonmineral Nutritional Supplements - Nabavi, Seyed Mohammad; Silva, Ana Sanches (London, United Kingdom : ACADEMIC PRESS, An imprint of Elsevier, 2019)
Nonvitamin and Nonmineral Nutritional Supplements compiles comprehensive information and recent findings on supplements found in today's market. The book focuses on non-essential nutrients, animal extracts, yeast and fungi extracts, and plant and algae extracts used as supplements. Readers will find valuable insights on the impact of dietary supplementation on human health, along with an understanding of the positive and negative aspects of each supplement.
Includes bibliographical references and and index.
Keywords: Dietary supplements; Nutrition; Health